Researching religion and migration 20 years after ‘9/11’: Taking stock and looking ahead - Fleischmann, Fenella (Zeitschrift für Religion, Gesellschaft und Politik, 2022)
This contribution to the special issue on religion and migration reviews two decades of large-scale survey research on changes in immigrant religion and the relationship between immigrants’ level of religiosity and their integration into European societies. The body of work reveals that Muslims in European societies stand out due to their comparatively high levels of religiosity and greater stability in religiosity over time and across immigrant generations. While the comparative picture is rather clear, findings regarding the long-term trend in Muslims’ religiosity and its association with immigrant integration are instead inconclusive. A systematic review of empirical studies of the association of (various indicators of) individual religiosity with immigrant integration reveals positive, negative and non-significant results for all outcomes and domains. Thus, based on the current state of art it is hard to assess whether and why religion forms a bridge or barrier to immigrant integration in Europe. To move the field forward, the contribution ends with a twofold proposal for a research agenda that includes a broadened empirical scope, moving beyond the focus on Sunni Muslims, and a conceptual extension that focuses on differences in reasoning about religion and religious meaning-making as additional, potentially more consistent and more powerful explanation for immigrants’ social relations and positions in their new societies